International Humanitarian Law under Pressure: Legal Responses to 21st Century Armed Conflicts - Hermansyah (Indonesian Scientific Publication, 2024)
This narrative review explores the evolution of International Humanitarian Law (IHL) in the context of contemporary armed conflicts, focusing on five key areas: technological innovation, gender-based protection, humanitarian intervention, urban warfare, and non-state actors. The study begins by framing the urgency to reevaluate IHL as conflicts become increasingly complex due to technological advancement and hybrid threats. The literature was collected from databases such as Scopus and Google Scholar using specific keywords including